Anti-Apoptotic Bfl-1 Is the Major Effector in Activation-Induced Human Mast Cell Survival - Ekoff, Maria (Public Library of Science, 2012)
Mast cells are best known for their role in allergic reactions, where aggregation of FcεRI leads to the release of mast cell mediators causing allergic symptoms. The activation also induces a survival program in the cells, i.e., activation-induced mast cell survival. The aim of the present study was to investigate how the activation-induced survival is mediated. Cord blood-derived mast cells and the mast cell line LAD-2 were activated through FcεRI crosslinking, with or without addition of chemicals that inhibit the activity or expression of selected Bcl-2 family members (ABT-737; roscovitine). Cell viability was assessed using staining and flow cytometry. The expression and function of Bcl-2 family members BFL-1 and MCL-1 were investigated using real-time quantitative PCR and siRNA treatment. The mast cell expression of Bfl-1 was investigated in skin biopsies. FcεRI crosslinking promotes activation-induced survival of human mast cells and this is associated with an upregulation of the anti-apoptotic Bcl-2 family member Bfl-1. ABT-737 alone or in combination with roscovitine decreases viability of human mast cells although activation-induced survival is sustained, indicating a minor role for Bcl-XL, Bcl-2, Bcl-w and Mcl-1. Reducing BFL-1 but not MCL-1 levels by siRNA inhibited activation-induced mast cell survival. We also demonstrate that mast cell expression of Bfl-1 is elevated in birch-pollen-provocated skin and in lesions of atopic dermatitis and psoriasis patients. Taken together, our results highlight Bfl-1 as a major effector in activation-induced human mast cell survival.